Dielectric strength test to protection elements for live lines works - Pinto-Salamanca, Carlos Eduardo; Castro-Galeano, Juan Carlos (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2017)
This paper presents the design and assembly of a system of tests of sustained voltage to elements and equipment used in live line maneuvers through tests on gloves and dielectric rods, as these are the first points of contact to ensure safe operations. It means an advance for the creation of a laboratory certified in this type of tests at Universidad Pedagógica y Tecnológica de Colombia (UPTC) Faculty of Duitama, considering that currently there are not laboratories that provide this service in Boyacá and Casanare. Dielectric strength tests were performed on personal protection elements and equipment under the parameters of ASTM D120, ASTM F496, ISO 60903, ASTM-F711 and IEEE 978, developing an assembly for testing gloves and dielectric rods with voltage levels up to 15 kV. The results validate the proposed system to outlook of circuit design and implementation, where tests were performed to establish dielectric capacities, in operating under open circuit conditions, with resistive load or short circuit. The compliance with the regulations established under the test sequences of safety parameters for the system and the follow-up to the tests was verified through the use of a management system for the generation of concepts of approval or rejection of the tested elements.